Effects of physical activity on visuospatial working memory in healthy individuals: A systematic review and meta-analysis - Zhu, Qiqi; Deng, Jie; Yao, Meixi; Xu, Chong; Liu, Demin; Guo, Liya; Zhu, Yu (Frontiers in Psychology, 2023)
Physical activity interventions improve cognitive performance, especially visuospatial working memory (VSWM). However, evidence on the effects of these interventions in children and adolescents, and in older adults, remains scant. This meta-analysis aimed to identify the effects of physical activity on VSWM improvement in healthy individuals and the best exercise intervention program to improve VSWM capacity. We searched for randomized controlled trials (RCTs) of exercise interventions targeting VSWM in healthy individuals from Web of Science, MEDLINE, BIOSIS Previews, PubMed, China National Knowledge Infrastructure, and Wanfang Data (Chinese) databases, from inception to August 20, 2022. Among 21 articles (1595 healthy subjects), the heterogeneity test statistic was I2 = 32.3%, P = 0.053. The mean quality scores of the included articles were 6.9 points (reaction time [RT] studies) and 7.5 points (Score studies). Moreover, 28 RCTs were included (10 RT studies and 18 Score studies), and the subgroup analysis found significant effects for elderly participants, children, interventions involving a higher level of cognitive engagement, low and moderate exercise intensity, chronic exercise, exercise duration ≥60 minutes, and exercise period ≥90 days. Physical activity had a small but significant positive impact on VSWM in healthy individuals. Current evidence confirms the effects of physical activity on VSWM capacity only in children and seniors, but not in young adults. Other age groups, including adolescents and middle-aged adults, have not been studied. Prescription of interventions involving high-level cognitive engagement, low and moderate exercise intensity, chronic exercise, exercise for >30 minutes per session, and exercise for more than three months is recommended for children and seniors.